Analysis of DoS attacks on Docker inter-component stdio copy - Tianyu ZHOU; Wenbo SHEN; Nanzi YANG; Jinku LI; Chenggang QIN; Wang YU (网络与信息安全学报)
In recent years,Docker has been widely deployed due to its flexibility and high scalability.However,its modular design leads to the DoS attacks on inter-component communication.A new DoS attack that outputs to stdout,causing high CPU usages among different Docker components.Analysis shows that the stdout output triggers the goroutines of Docker components.To find all goroutines setup paths,using the static analysis method to analyze the Docker components systematically was proposed.A static analysis framework was designed and implemented,and evaluated on Docker source code.The results show that static analysis framework finds 34 paths successfully,while 22 of them are confirmed by runtime verification.